Intrinsic Factors Influencing the Infection by Helminth Parasites in Horses under an Oceanic Climate Area (NW Spain). (23rd March 2009) - Francisco, I.; Arias, M.; Cortiñas, F. J.; Francisco, R.; Mochales, E.; Dacal, V.; Suárez, J. L.; Uriarte, J.; Morrondo, P.; Sánchez-Andrade, R.; Díez-Baños, P.; Paz-Silva, A.
Abstract : A coprological survey to determine the influence of some intrinsic factors (breed, age, and sex) on the infection by helminth parasites in equine livestock (n = 418 ) under an oceanic climate area (NW Spain) was conducted. Faecal samples were individually collected and analyzed by the coprological techniques. The main strongylid genera identified were Trichonema and Cyalocephalus spp (small strongyles) and Strongylus and Triodontophorus (large strongyles). The prevalence of gastrointestinal nematode was 89% (95% CI 86, 92) and 1% cestoda (0, 2). The percentage of horses with strongyloid parasites was 89% (86, 92), 11% (8, 14) for Parascaris, and 3% (1, 5) for Oxyuris . The highest prevalence for ascariosis was observed in the youngest horses (<3 years), for oxyurosis in the >10 years animals, and for strongylosis in the 3–10 years ones. Females were significantly more parasitized than males. A negative correlation between the age and the egg-excretion of ascarids and strongyles was recorded. The autochthonous and the English Pure Blood horses were the most parasitized. We concluded that the infections by helminths, especially the strongyloids, are significantly common in the region, so that greater importance should be given to this situation.